After the last post the lives of Indian historiography - Zachariah, Benjamin 1972- (De Gruyter Oldenbourg, 2019)
This book is about the production and consumption of history, themes that have gained in importance since the discipline's attempts to disavow its own authority with the ascendancy of postmodern and postcolonial perspectives. Several parallel themes crosscut the book's central focus on the discipline of history: its intellectual history, its historiography, and its connection to memory, particularly in relation to the need to establish the collective identity of 'nation', 'community' or state through a memorialisation process that has much to do with history, or at least with claiming a historicity for collective memory. None of this can be undertaken without an understanding of the roles that history-writing and history-reading have been made to perform in public debates, or perhaps more accurately in public disputes. The book addresses a discomfort with postcolonial theories in and as history. Following are essays that examine the state of the discipline, the art of reading and using archives, practices of tracking the history of ideas, and the themes of history, memory and identity
Keywords: Geschichte; Historiographie; Identität; Indien; Internationale Geschichte; Postkolonialismus; HISTORY / General; Geschichtsschreibung